Public Opinion and Military Intervention: Afghanistan, Iraq and Libya. Issue 1 (14th February 2013) - Clements, Ben
Abstract Britain has participated in several military interventions of varying duration, extent and political controversy in recent years. This article analyses public opinion towards the most recent intervention in Libya in 2011, looking at three different aspects of the topic. First, it examines differences in cross‐national attitudes towards military action in Libya amongst NATO countries. Secondly, it then looks in detail at which social groups were more or less likely to approve of British involvement, comparing this with group attitudes towards Britain's role in Afghanistan and Iraq. Thirdly, it assesses how public opinion shifted during the course of the action in Libya, looking at three key indicators of the popular mood: whether Britain was right or wrong to take military action; how well the war is going; and assessments of David Cameron's handling of the conflict. Broader reflections are then made about public opinion towards British involvement in future military action.